Molecular identification of sex in Simarouba glauca by RAPD markers for crop improvement strategies - Vaidya, Gayatri (Biotechnol Rep (Amst), 2014)
Due to lack of morphological methods to identify sex at early stage in the plants with long juvenile period the application of molecular markers is expected to facilitate breeding program. The objective of this study is to identify molecular markers linked to sex determination of the plant Simarouba glauca which assists in crop improvement program. Random amplified polymorphic DNA primers were tested on dioeceious and hermaphrodite plant Simarouba glauca. A set of eighty five RAPD primers were screened out of which only five primers were found to be associated with sex. The primer OPU-10 is male specific and OPD-19 primer is female specific. Another primer OPU-19 produced a unique amplification in only hermaphrodite individuals. Female and hermaphrodite specific primer OPS-05 amplified an amplicon in female and hermaphrodite and was absent in male plant. Primer OPW-03 produced amplicon specific to male and hermaphrodite plants and was absent in female plants.